COMMUNICATION STRATEGIES AND TACTICS IN CRISIS SITUATIONS - Olena Danylina (Інтегровані комунікації, 2025)
A comprehensive review of Ukrainian and international literature on the transformation of the crisis environment and the media’s role in covering it deepens our understanding of the multilevel nature of contemporary crises, from global economic shocks to local reputational disruptions. Drawing on content analysis of emblematic cases (COVID-19, the Suez Canal blockage, Russian propaganda campaigns, etc.) and synthesising the ideas of K. Schwab, J. Séguéla, M. Pavlovsky, P. Kukhta, and others, the study outlines key drivers of information turbulence that weaken traditional hierarchical communication models. Methods of analysis and synthesis were applied to systematise crisis classifications by scale, subject matter, causes, and structural features; a diachronic review traced the evolution of media strategies from post-crisis reporting to proactive, real-time networked responses. The case-study analysis identified three overarching tactics of media behaviour: operational–informational (rapid dissemination of verified facts), analytical–interpretative (contextual explanation of cause-and-effect links), and mobilisation-oriented (stimulating collective action). Their optimal mix depends on crisis dynamics, while maximum effectiveness requires transparent sourcing, coordination with official bodies, and algorithmic content monitoring. The study generalises that the digital revolution imposes new demands on editorial practice: integrating social platforms as primary information channels, accelerating fact-checking cycles, and engaging audiences in participatory verification. It concludes that a hybrid crisis-communication model—combining the ethical foundations of traditional journalism with instantaneous digital interaction — can reduce information risks and reinforce public trust throughout all phases of the crisis cycle. Further research is needed to typologise tools for countering disinformation in today’s multi-channel media ecosystem.